Investigations of ageing mechanism and electrical withstand performances of the field aged 132 kV PMU Skudai's ceramic post insulator - Thazali, Nur Athirah (2013)
This thesis presents investigation of 132kV field-aged ceramic post insulator, which has been in service 15 years old on a 132kV in PMU Skudai substation. Insulators are devices which are used in electricity supply networks to support, separate or contain conductors at high voltage. Aging of ceramic and post insulator materials is reviewed mainly from the standpoint of their interfacial performance. Insulating materials can be divided into simple ceramics. Aging processes are complicated in general, and take place under simultaneous multiple stresses such as electrical, mechanical and environmental stresses. Contact angle measured insulation under consideration leads to the surface is approximately horizontal to the top surface. The sheds also aged differently around their circumference and this is reflected in discoloration differences on different sides of the insulator, in addition to hydrophobicity changes. Voltage breakdown measurements carried out in the laboratory are also presented. Material analysis shows oxidation of the surface. Ageing effects were different uniform for each shed, the greatest oxidation being on the top surfaces of the sheds on the west and east side. Microscopy was found to be the most useful and effective tools for analysis of these ceramic insulator. The measurements of the various parameters over the whole surface of the insulators are found to be consistent with each other and can be interpreted in terms of the chemistry of ageing and the longer term performance of the specific insulators in question. Two distinct types of ageing are identified. The role of solar radiation appears critical. In summary, the post insulators which have been in service for 15 years have very non-uniform surface properties in both the vertical and circumferential directions. There are some surface area at insulator has a moisture contamination at each creepage where found at all direction.